2018
DOI: 10.1002/2211-5463.12538
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of a novel vincristine‐resistant diffuse large B‐cell lymphoma cell line containing the 8q24 homogeneously staining region

Abstract: Chromosome band 8q24 is the most frequently amplified locus in various types of cancers. MYC has been identified as the primary oncogene at the 8q24 locus, whereas a long noncoding gene, PVT 1 , which lies adjacent to MYC , has recently emerged as another potential oncogenic regulator at this position. In this study, we established and characterized a novel cell line, AMU ‐ ML … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Recently, a novel cell line, named AMU-ML2, characterized by the occurrence of a homogeneously staining region at the 8q24 locus and containing more than 20 copies of the entire MYC and PVT1 genes, has been established from a DLBCL patient at diagnosis. Of note, AMU-ML2 cells expressed elevated levels of MYC, PVT1 and circPVT1 and were resistant to vincristine, suggesting a potential link between PVT1 and drug resistance in DLBCL [64]. This hypothesis is in line with previous reports on PVT1-mediated resistance to cisplatin in gastric and ovarian cancers [87].…”
Section: Lymphomassupporting
confidence: 89%
See 1 more Smart Citation
“…Recently, a novel cell line, named AMU-ML2, characterized by the occurrence of a homogeneously staining region at the 8q24 locus and containing more than 20 copies of the entire MYC and PVT1 genes, has been established from a DLBCL patient at diagnosis. Of note, AMU-ML2 cells expressed elevated levels of MYC, PVT1 and circPVT1 and were resistant to vincristine, suggesting a potential link between PVT1 and drug resistance in DLBCL [64]. This hypothesis is in line with previous reports on PVT1-mediated resistance to cisplatin in gastric and ovarian cancers [87].…”
Section: Lymphomassupporting
confidence: 89%
“…No transforming ability of PVT1 and circPVT1 per se has been demonstrated in hematopoietic cells so far, suggesting a role in tumor progression and in support of a proliferative phenotype, rather than in cancer development. Moreover, some new insights on the role of PVT1 in drug response are emerging, including the elevated expression of both PVT1 and circPVT1 in the vincristine-resistant AMU-ML2 DLBCL line [64] and the glucocorticoid-resistant phenotype promoted by circPVT1 in MM models, that is rescued by knockdown [70]. Although some of these data need to be substantiated by scientific publications, they provide a clear path to go in hemato-oncology, where targeting of PVT1 and/or circPVT1 may a be a valuable option for combination therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of PVT1 inhibited cell proliferation and arrested cell cycle at G1 stage via recruiting EZH2 (zeste homolog 2) and regulating p15 and p16 epigenetically (28). Moreover, some new insights on the role of PVT1 in drug response are emerging, including the elevated expression of PVT1 in the vincristine-resistant AMU-ML2 DLBCL line (48). Recently, the research performed by Li et al confirmed that the downregulated expression of H19 increased the efficacy of temozolomide (TMZ) chemotherapy in glioblastoma multiforme (GBM) cells (49).…”
Section: Discussionmentioning
confidence: 99%
“…As a heterogeneous disease, DLBCL can be classified into activated B-cell, germinal center B-cell, and primary mediastinal B-cell subtypes based on gene expression profiling [21]. Though about 70% of DLBCL patients have survival time longer than five years when treated with immunochemotherapy involving rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisolone (R-CHOP) [22], however, the remaining patients are still dying of this malignant tumor. In addition, the short-and long-term toxicity of chemotherapy, including secondary malignancies and leukemia, adversely affects the long-term prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%